Comprehension of paraquat adsorption on faujasite zeolite X and Y in sodium form - Wina Rongchapo; Chalermpan Keawkumay; Nattawut Osakoo; Krittanun Deekamwong; Narong Chanlek; Sanchai Prayoonpokarach; Jatuporn Wittayakun (Adsorption Science & Technology)
The nature of paraquat adsorption is compared between zeolite NaX and NaY which have the same faujasite structure but different Si/Al ratio, namely 1.2 and 2.2, respectively. The adsorption was proposed to occur via ion exchange and expected to increase with Al content. However, NaX had a lower paraquat adsorption capacity than NaY. The bare and paraquat-containing zeolites (PQX and PQY) were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, N 2 adsorption–desorption analysis, magic-angle spinning nuclear magnetic resonance (MAS) NMR, and X-ray photoelectron spectroscopy. The presence of adsorbed paraquat was confirmed by Fourier transform infrared spectroscopy. Paraquat adsorbed in supercages of the zeolites resulting in a decrease of surface area and displacement of sodium cations. Results from 23 Na MAS NMR and X-ray photoelectron spectroscopy indicated that interaction of sodium ions in the cavity of NaX was stronger than that in NaY, making it less exchangeable with paraquat.